Traumatic Life Events in Relation to Cognitive Flexibility: Moderating Role of the BDNF Val66Met Gene Polymorphism - Gabrys, Robert L.; Dixon, Kaylyn; Anisman, Hymie (Frontiers in Behavioral Neuroscience, 2017)
Cognitive flexibility plays an important role in an individual’s ability to adapt to a continuously changing environment and is considered central to goal-oriented behavior. Accordingly, increasing attention has been devoted to understanding the factors, including genetic and early life experiences, which might contribute to individual differences in this ability. In the present investigation, we examined the contribution of the BDNF Val66Met polymorphism to cognitive flexibility, as assessed by set-shifting ability on Wisconsin Card Sorting Task (WCST), and whether this polymorphism moderated the relation between trauma experiences (including type and timing of trauma occurrence) and cognitive flexibility. Among undergraduate students (N = 239), greater frequency of total traumas experienced prior to the age 5 was associated with greater difficulties in set-shifting (as indexed by more frequent perseverative errors on the WCST) among individuals carrying the Met allele of the BDNF polymorphism, but not those who were Val homozygotes. By contrast, total traumas experienced between the age of 6 to 12 and 13 to 18 were not related to set-shifting ability, and these relations were not moderated by BDNF genotype. Moreover, greater frequency of general traumas and emotional abuse was associated with set-shifting difficulties for both male and female Met allele carriers, but not Val homozygotes. In contrast, physical punishment was related to difficulties in set-shifting, but only among male Met carriers, an effect that was likely attributed to greater frequency of this form of trauma among males. The present findings suggest that the relationship between early life trauma and later-life cognitive flexibility might depend on the presence of the BDNF Val66Met polymorphism as well as the development stage at which the trauma has occurred. Moreover, the present investigation provides further understanding into the factors (i.e., genetic and early life experiences) that might be associated with individual differences in cognitive functioning and goal-directed behaviors, such as problem-solving and decision-making.